From egg to slaughter: monitoring the welfare of Nile tilapia, Oreochromis niloticus, throughout their entire life cycle in aquaculture - Pedrazzani, Ana Silvia; Cozer, Nathieli; Quintiliano, Murilo Henrique; Tavares, Camila Prestes dos Santos; Biernaski, Vilmar; Ostrensky, Antonio (Frontiers in Veterinary Science, 2023)
This study assesses the welfare of Nile tilapia (Oreochromis niloticus) throughout their entire life cycle in aquaculture, from reproduction to slaughter. The work was structured based on identifying welfare indicators that directly align with the animal freedoms established by the Farm Animal Council: environmental, health, nutritional, and behavioural freedom and psychological, being the later, psychological freedom, intrinsically considered in the behavioural and physical analyses of the animals. We conducted an integrative systematic literature review to define specific indicators and their reference values for each phase of tilapia cultivation. The reference values were then classified based on a scoring system, which evaluates the variation of each indicator within the ranges considered ideal (score 1), tolerable (score 2), and critical (score 3) for the welfare of the target species. We conducted a laboratory experiment to validate the pre-selected health indicators for the early life stages of tilapia. This experiment allowed us to assess the applicability of the indicators under operational conditions. Based on these results, we proposed Partial Welfare Indices (PWI) for each evaluated freedom and the General Welfare Index (GWI) calculated from the PWI. These indices were calculated using mathematical equations that propose a quantitative and standardised welfare index, allowing tilapia farmers and processors to monitor and improve their production systems. Simultaneously, it contributes to ensuring the welfare of farmed fish and promoting the implementation of more sustainable and ethical practices in the tilapia production process in aquaculture.